The Improvement of Studentsâ Understanding about Sociology Materials by Using Index Card Match Strategy - Mustolikh, Mustolikh (EDUCARE, 2010)
ABSTRACT: This research is aimed at improving the understanding of semester II students of Geography Education about sociology materials. This is a development and improvement of learning quality research (PPKP). The subject of this research is 23 students of semester II of class A, Geography education, Muhammadiyah University of Purwokerto, academic year of 2008-2009. This research is conducted in three cycles. Each cycle consists of planning, acting, observing and reflecting. Time allocation for action is 2 x 50 minutes of teaching and learning process for each cycle. The data is collected by conducting observation, interview and test. The data is analyzed by using descriptive quantitative method and percentage technique with the target of more than 75% students can achieve mastery learning. The average of students understanding about sociology materials increases from cycle 1 meeting (65, 23%)Â to cycle 2 meeting (74%) and from cycle 2 meeting (74%) to cycle 3 meeting (82,61%). Based on the result above, it can be concluded that the understanding of semester II of class A students of Geography education about Sociology materials can be improved by using âIndex Card Matchâ.KEY WORDS: improvement, studentsâ understanding, strategy in teaching and learning process, and sociology materials.===About the Author: Mustolikh, M.Si. is a Lecturer at the Department of Geography Education, Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh PO Box 202, Purwokerto 53182, Central Java, Indonesia. For academic purposes, he can be reached at: mustolikh@ymail.comHow to cite this article? Mustolikh. (2010). âThe Improvement of Studentsâ Understanding about Sociology Materials by Using Index Card Match Strategyâ in EDUCARE: International Journal for Educational Studies, Vol.2(2) February, pp.223-228. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 1, 2009); Revised (January 10, 2010); and Published (February 17, 2010).